2020
DOI: 10.1515/teme-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Generation of tailored subsurface zones in steels containing metastable austenite by adaptive machining and validation by eddy current testing

Abstract: In order to withstand high mechanical and tribological loads, it is important that the components not only have a high core ductility but also a hard surface. Typically, a suitable microstructure is created by heat treatment processes before the workpiece is machined. However, these processes are time and energy consuming and can lead to component distortion. It would therefore be of great advantage if no additional heat treatment process would be required to produce a hardened subsurface zone. Since turning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nevertheless, in another study, it was found that the phase of the first harmonic is more pronounced to the influence of the eddy current sensor–workpiece distance. [ 39 ] Hence, if there are any changes in geometrical arrangement, it might lead to a misinterpretation of the martensite content. Therefore, it would be preferable to use another parameter to detect the martensite content.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in another study, it was found that the phase of the first harmonic is more pronounced to the influence of the eddy current sensor–workpiece distance. [ 39 ] Hence, if there are any changes in geometrical arrangement, it might lead to a misinterpretation of the martensite content. Therefore, it would be preferable to use another parameter to detect the martensite content.…”
Section: Resultsmentioning
confidence: 99%
“…These findings motivate the use of eddy current testing for setting a desired fraction of martensite in process control. The required process parameters can be calculated by using a quantitative regression model for the martensite generation, published in [39].…”
Section: Measurement Of Surface Layer Statesmentioning
confidence: 99%
“…Uebel et al [40] proposed a soft sensor based on force, temperature, pneumatic, and angle resolved scattered light sensor measurement. Fricke et al [58][59][60] developed an eddy current sensor measurement in combination with a cutting simulation for the online prediction of martensite content during turning.…”
Section: Introductionmentioning
confidence: 99%